Evaluation of the economic impact of a national lymphoedema service in Wales - Ioan Humphreys (British Journal of Nursing, 2017)
Lymphoedema Network Wales has focused on maximising the impact ofits service through the effective use of available resources to ensure highqualityand consistent care for people with lymphoedema across Wales. Theaim of this evaluation was to estimate the economic impact of a nationallymphoedema service on the NHS Wales budget. Work was undertaken todetermine the care pathway within Lymphoedema Network Wales and developa hypothetical ‘world without’ the service as a comparator. The four groupsof patients that made up the pathways were Group 0: ‘at risk’, Group 1-2:‘uncomplicated lymphoedema’, Group 3: ‘complicated/complex’ and Group4: ‘palliative care’. Overall resource utilisation between 6 months pre- and6 months post-entry indicated that there were significant cost reductions tobe seen after lymphoedema service entry for all patients in each group. Thisevaluation provides estimates that suggest that the service is likely to be costsaving when people with lymphoedema are managed within LymphoedemaNetwork Wales rather than in a ‘world without’ the service.